BS EN 253 AMD1. District heating pipes. Bonded single pipe systems for directly buried hot water networks. Factory made pipe assembly of steel service pipe, polyurethane thermal insulation and a casing of polyethylene. (16th June 2022) - British Standards Institution,
No abstract available